Keep customers coming back: Enhancing value and satisfaction in a mobile shopping application context - Naquita Fernandes; Catherine Barfknecht (Cogent Business & Management, 2020)
Mobile shopping applications have become a popular channel to reach the omnipresent consumer of today. However, the market space has become highly competitive and as a consequence, cultivating repurchase behavior has become pivotal to retain market share and boost sustainability. While the literature regarding initial purchase via a mobile shopping application is well developed, knowledge of how to foster repurchase behavior in this context is still scarce. In order to address the gap in extant literature, this research drew on the perceived value theory as well as technology acceptance and continued usage literature to conceptualize how repurchase intentions can be elicited. An online survey was administered to a total of 245 consumers who had previously shopped via a mobile shopping application, using a non-probability convenience sampling approach. Partial least squares structural equation modelling was used to test cause-effect relationships in the model. The results verify the importance of primarily designing an entertaining and easy-to-use mobile shopping experience, followed by integrating atmospherics of trust and informative content. The amalgamation of these atmospherics lead to a value-infused end-user experience, enhancing user satisfaction. Lastly, the findings confirm that the satisfaction derived from the use of a mobile shopping application is a crucial determinant of repurchase intent. In summation, this study provides novel insights in terms of the context-specific nature of perceived value and its relation to satisfaction. Furthermore, the scarcity of research regarding the facilitation of repurchase behavior in a mobile shopping application context, is addressed.
Keywords: 650; digital atmospherics; digital satisfaction; hedonic value; mobile shopping applications; repurchase intention; utilitarian value